Antibacterial effects of kaempferol-loaded silver nanoparticles (AgNP-K) against Streptococcus mutans and Escherichia coli - Rohazila Mohamad Hanafiah; Nur Izyan Salihah Azmi; Dayang Siti Hazwani Abang Mat Ali; Siti Aisyah Abd Ghafar; Zulaiha A Rahman; Nur Fatimah Zaharah Salehuddin; Muhammad Khairin Mohd Hanafiah; Noor Akmar Nam; Rina Haryani Osman Basah (Universiti Sains Islam Malaysia, 2026)
Indexed by ERA/MYCITE